1998
DOI: 10.1128/mcb.18.10.5771
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in RNA Polymerase II and Elongation Factor SII Severely Reduce mRNA Levels in Saccharomyces cerevisiae

Abstract: Elongation factor SII interacts with RNA polymerase II and enables it to transcribe through arrest sites in vitro. The set of genes dependent upon SII function in vivo and the effects on RNA levels of mutations in different components of the elongation machinery are poorly understood. Using yeast lacking SII and bearing a conditional allele of RPB2, the gene encoding the second largest subunit of RNA polymerase II, we describe a genetic interaction between SII and RPB2. An SII gene disruption or the rpb2-10 mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 56 publications
4
64
0
Order By: Relevance
“…It was previously shown that cells lacking Taf14p have a mild decrease in constitutive and induced transcription levels in vivo (Henry et al 1994), while cells disrupted in PPR2 do not exhibit overall decreased transcription levels (Lennon et al 1998). In combination with a PPR2 disruption, cells with disruptions in Figure 2.-A taf14D allele is synthetically lethal in combination with a ppr2D allele.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously shown that cells lacking Taf14p have a mild decrease in constitutive and induced transcription levels in vivo (Henry et al 1994), while cells disrupted in PPR2 do not exhibit overall decreased transcription levels (Lennon et al 1998). In combination with a PPR2 disruption, cells with disruptions in Figure 2.-A taf14D allele is synthetically lethal in combination with a ppr2D allele.…”
Section: Resultsmentioning
confidence: 99%
“…2B. Here, however, a different laboratory strain of yeast was used in which the DST1 gene was disrupted by a hisG cassette (10). The paromomycin experiment shows that the assay was able to detect the induction of full-length active luciferase from transcripts containing a stop codon at position 445.…”
Section: Detection Of Active Luciferase Enzyme By Induction Of Translmentioning
confidence: 99%
“…Cells lacking SII are defective in transcriptional induction of a number of genes (10,12,35). To ensure that the luciferase activity determinations were not biased by a difference in luciferase mRNA levels between the DST1 deletant and cells wild-type for DST1, we measured the amount of transcript by Northern blotting (data not shown).…”
Section: Luc-⌬ and 2ϫ Stop)mentioning
confidence: 99%
See 1 more Smart Citation
“…If this reflects increased competition by the downstream 3Ј splice site due to additional time for elongating polymerase to complete the downstream intron, then slowing of RNA polymerase should have the opposite effect and should suppress exon skipping (enhance exon inclusion). To test this, we used two mutations in the gene encoding the second largest subunit of RNAP II, RPB2, because multiple lines of evidence implicate this subunit in the process of transcript elongation (Treich et al 1992;Powell and Reines 1996;Lennon et al 1998). One mutant, rpb2-10, has been shown to exhibit a reduced rate of transcript elongation in vitro (Powell and Reines 1996).…”
Section: Rnap II Mutants Suppress Exon Skippingmentioning
confidence: 99%